ANALISA KOMPILASI HUKUM EKONOMI SYARIAH DAN FATWA DEWAN SYARIAH NASIONAL PERSPEKTIF SOSIOLOGI HUKUM - Yumna, Laila; Taufik, Azhar (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2023)
The presence of Islamic financial institutions (LKS) which is quite massive, makes Islamic economic operational activities must have the nature of legal certainty. At present, specifically the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) can be said to be material law in the sharia economy. Meanwhile, the Sharia Economic Law Compilation (KHES) is a formal and material law as a reference for judges at the Religious Courts in resolving sharia economic disputes. This research is a library research with a sociological approach. Where the purpose of this writing is to analyze KHES and DSN-MUI fatwas in providing space for the development of the Islamic economy through the synergy between the two in the perspective of legal sociology. The results of the research concluded that the existence of KHES was based on PERMA No. 2 in 2008 as a guideline and is binding on judges in the religious court in resolving the economic affairs of the Syrian regime. While the DSN MUI fatwa is bound to Syrian economic activities based on the absorption of fatwa-fatwa to the regulations of legislation such as PBI, PMK or SEOJK. On the basis of this, it causes KHES to have a higher position than DSN fatwa. Therefore, the fatwa issued by the DSN MUI should